2005
DOI: 10.1128/jvi.79.15.9694-9701.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Heterologous Prime-Boost Regimens Involving Recombinant Adenovirus Serotype 11 (Ad11) and Ad35 Vaccine Vectors in the Presence of Anti-Ad5 Immunity

Abstract: The high prevalence of preexisting immunity to adenovirus serotype 5 (Ad5) in human populations will likely limit the immunogenicity and clinical utility of recombinant Ad5 (rAd5) vector-based vaccines for human immunodeficiency virus type 1 and other pathogens. A potential solution to this problem is to utilize rAd vaccine vectors derived from rare Ad serotypes such as Ad35 and Ad11. We have previously reported that rAd35 vectors were immunogenic in the presence of anti-Ad5 immunity, but the immunogenicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
120
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 32 publications
9
120
0
Order By: Relevance
“…A number of DNA prime-adenovirus boost regimens were intended to induce cellular immune responses through intramuscular injection [42][43][44][45][46][47][48][49]. Some research groups, however, reported that DNA prime-virus boost regimens stimulated strong humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A number of DNA prime-adenovirus boost regimens were intended to induce cellular immune responses through intramuscular injection [42][43][44][45][46][47][48][49]. Some research groups, however, reported that DNA prime-virus boost regimens stimulated strong humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenicity of rAd, together with the availability of a highly efficient and scalable production platform (17,21), has fuelled interest in pursuing Ad vectors as a vaccine platform. The preexisting neutralizing immunity limits the use of highly prevalent serotypes, such as Ad serotype 5 (Ad5) (2,10,11,14,19,28,31,42,57,58,60); however, the development of novel vectors based on low-seroprevalence serotypes that are not influenced by the preexisting immunity toward Ad5, such as Ad35 (1,4,60), open new avenues for the use Ad vectors as vaccine vehicles.…”
mentioning
confidence: 99%
“…While attenuation of IgA responses was eventually observed, the ability to immunize multiple times appears effective as a priming regimen for other vaccines or for the use of other serotypes of Ad [59][60][61][62]. Proof of principle is demonstrated here where mucosal oral priming of macaques by oral Ad administration was followed by mucosal boosting with an intranasal peptide vaccine.…”
Section: Discussionmentioning
confidence: 91%